(untitled) - Gage,Tommy W. (St. Louis, MO, 2006)
This sectiom of the book features drugs classified by primary therapeutic or pharmacologic group, or both. Thus you can locate drugs by knowing their primary therapeutic use or general pharmacologic class.
Keywords: Dental pharmacology.,Dược lý học nha khoa